Fun and Play Learning Model for Children with Special Needs - Agung Prasetyo, Asrowi, Nunuk Suryani dan Sunardi (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Education is an effort to develop human potential optimally, both in terms of physical,mental, social and spiritual in accordance with the uniqueness of each individual. Througheducation is expected every child is able to develop their potential optimally. This is notonly applicable to children in general but is no exception applicable to children with specialneeds.One of those included in children with special needs is children with autism spectrumdisorders, who have developmental barriers in communication, social interaction andbehavior. Some children with autism spectrum disorders do not care what they do. Theyimitate another child without having a reason to do so. Barriers to children should beminimized so that the potential of children can develop optimally. The product resultingfrom the development of this learning model is a model of learning that can be used forespecially Autis with difficulty of its form disruption speech ability.Things that distinguish this learning model is implemented in accordance with thecharacteristics of the child's own method of Fun and Play or learn a fun by playing. Theyare not afraid or feel comfortable because they can not understand whether there is undertreatment. The expected product is a module with a syntax or stage based on fun activities(Fun and Play).Children with Special Needs are unique personalities, sometimes behind their uniquenessstored pearl abilities, where we can not see or label how much they can before we givethem the best treatment. Autism with any spectrum should immediately get the right serviceand no mistreatment because if it had been indicated autistic as far as are knowledge willlead to Schizhoprenia behavior because both have almost similar characteristics .Keywords : fun and play, children with special needs, autism spectrum , disruption speech ability,schizhoprenia